Pemaknaan Mahasiswa STDI Imam Syafi’i Jember terhadap Peran Fikih Ṭalāq dalam Membentuk Kesiapan Berumah Tangga: Perceptions of Students at STDI Imam Syafi’i Jember Regarding the Role Ṭalāq Jurisprudence in Preparing Them for Married Life - Nauroh Nafi'ah; Emha Hasan Amiinulloh Asy'ari (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2026)
Divorce rates in Indonesia remain concerning, partly due to limited understanding of ṭalāq (divorce) jurisprudence as part of premarital education. This study aims to analyze the concept of fiqh ṭalāq in Islam and explore how male and female students at STDI Imam Syafi’i Jember interpret the role of understanding ṭalāq jurisprudence in shaping marital readiness. A qualitative approach was employed involving thirteen informants (eight female and five male students) from the Islamic Family Law study program who had comleted the Islamic Marriage Law 2 course. Data were collected through direct interviews and open-ended questionnaires, then analyzed using the Miles, Huberman, and Saldaña interactive model. The findings show that ṭalāq jurisprudence regulates various forms of marital dissolution, including raj'ī divorce, bā'in divorce, sunnī divorce, bid'ī divorce, īlā', and khulu'. Informants interpreted their understanding of ṭalāq jurisprudence as fostering caution toward divorce, a more realistic outlook on marriage, mental readiness and emotional control, as well as spiritual awareness and reponsibility in married life. Nevertheless, all informants emphasized that understanding ṭalāq jurisprudence alone does not determine marital readiness, which also requires emotional maturity, financial preparedness, and holistic social readiness. This study contributes to enriching Islamic family jurisprudence studies, particulary regarding the relationship between understanding divorce law and readiness to build household from both prospective husbands’ and wives’ perspectives.